Therapeutic interventions in vertigo management - Kameshwaran, Mohan; Sarda, Kushal (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Vertigo is a condition associated with a spectrum of symptoms and ~30% of general population experience vertigo in their life time. In spite of being of high clinical importance, the management of vertigo is quite challenging. Though the literature supports the availability of various therapeutic interventions used in vertigo treatment, their effectiveness depends on accurate diagnosis, appropriate use of intervention, and physician’s awareness of the overlap between vestibular, autonomic, and psychological aspects of vestibular pathology. Unfortunately, several drugs act as tranquilizers and impede the process of vestibular compensation. Betahistine, a histamine analogue, is one of the most commonly used anti-vertigo drugs worldwide and has been supported by many clinical trials. There have been several oral communications in international conferences on the efficacy of using betahistine in several clinical vertiginous syndromes. The current review assesses the use of betahistine 48 mg twice daily for three months as an efficient and well-tolerated treatment for vertigo. Additionally, it highlights the low incidence of side effects even at high doses of betahistine and suggests that it may be considered as the first-line of treatment for vestibular dysfunction.